2017
DOI: 10.1097/cad.0000000000000441
|View full text |Cite
|
Sign up to set email alerts
|

YM155 inhibits topoisomerase function

Abstract: YM155 (Sepantronium bromide) has been evaluated in clinical trials as a survivin suppressant but despite positive signals from early work later studies were negative. Clarifying the mechanism of action of YM155 is important to its further development. YM155 affects cells in a cell cycle specific manner. When cells are in G1, YM155 prevented their progression through S phase, leaving the cells at G1/S when exposed to YM155. Passage through mitosis from G2 is also defective following YM155 exposure. In this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 47 publications
(49 reference statements)
1
18
0
Order By: Relevance
“…The mechanism of action of YM155 as anticancer drug is still a matter of debate. Although initially proposed as a BIRC5 transcriptional repressor, YM155 has been subsequently shown to induce DNA damage [50] and to inhibit double-strand break repair [51] . In most of the carcinoma models, survivin inhibition induces apoptosis, whereas for MLS as well as for chondrosarcoma [20] , survivin expression was predominantly nuclear.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of action of YM155 as anticancer drug is still a matter of debate. Although initially proposed as a BIRC5 transcriptional repressor, YM155 has been subsequently shown to induce DNA damage [50] and to inhibit double-strand break repair [51] . In most of the carcinoma models, survivin inhibition induces apoptosis, whereas for MLS as well as for chondrosarcoma [20] , survivin expression was predominantly nuclear.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that the effect of YM155 on some of its targets in the IAP and Bcl-2 families could be cancer cell type-dependent. Interestingly, a study demonstrated that both YM155 and its structural analog NSC80467 induce a DNA damage response [46]; and a recent study even showed that YM155 inhibits topoisomerase 2α decatenation and topoisomerase 1 (Top1)mediated cleavage of DNA, suggesting that YM155 inhibits the Top1 enzyme activity [47]. Nevertheless, YM155 was much better than NSC80467 in terms of its potential to inhibit the expression of survivin [46].…”
Section: Inhibitors That Decrease Survivin Gene Transcriptionmentioning
confidence: 99%
“…al. [13] performed in an in vitro study of lung cancer showed that topoisomerase IIα (Top2α) was a target of YM155. Uncovering the effects and mechanism of YM155 in ATC is essential to predict patient response to therapy, identify synergistic drug combinations, and minimize toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…YM155 also targets interleukin enhancer-binding factor 3/NF110 in PC-3, Calu-6, and HeLa cells [ 12 ]. A recent report of YM155 by Hong et al [ 13 ] performed in an in vitro study of lung cancer showed that topoisomerase IIα (Top2α) was a target of YM155. Uncovering the effects and mechanism of YM155 in ATC is essential to predict patient response to therapy, identify synergistic drug combinations, and minimize toxicity.…”
Section: Introductionmentioning
confidence: 99%